FOREIGN COUNTRIES' EXPERIENCE IN ENSURING AND ASSESSING THE SOLVENCY OF INSURANCE ORGANIZATIONS - Xattabov Murodulla Batirovich (American Journals, 2026)
This article presents an analysis of the experience of foreign countries in ensuring and assessing the solvency of insurance organizations. In addition, proposals and practical recommendations aimed at the experience of foreign countries in ensuring and assessing the solvency of insurance organizations have been developed.
Keywords: Insurance market, insurance organizations, insurance payment, insurance premium, insurance money, insurance liability.